Management Strategy For New Product Development In Enhancing Company Competitiveness In The Digital Era - Hadi, Eko Supriyanto (JAKI : Jurnal Akuntansi, 2025)
Management strategy for new product development is a crucial factor in enhancing company competitiveness, particularly in the rapidly evolving digital era. Amidst increasing global competition, companies are required to continuously innovate and adapt relevant strategies to survive and thrive. New product development involves not only technical aspects but also the consideration of market demands, shifting consumer preferences, and the application of digital technologies that accelerate the innovation process. In this context, management strategy plays a vital role in formulating effective approaches, including market research, technology-based product development, and digital marketing that can increase customer engagement. This paper discusses how management strategy can be applied in new product development to strengthen a company’s competitiveness in a global market increasingly influenced by digital transformation. With the right approach, companies can respond to rapid changes and optimize existing market opportunities while mitigating potential risks. This research highlights the importance of integrating product development with management strategies based on digital technologies to achieve long-term success in an increasingly competitive business world.